2015
DOI: 10.1186/s12864-015-1929-y
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA detection by small RNA deep sequencing and disease association with myelodysplastic syndromes

Abstract: BackgroundAlthough advances in sequencing technologies have popularized the use of microRNA (miRNA) sequencing (miRNA-seq) for the quantification of miRNA expression, questions remain concerning the optimal methodologies for analysis and utilization of the data. The construction of a miRNA sequencing library selects RNA by length rather than type. However, as we have previously described, miRNAs represent only a subset of the species obtained by size selection. Consequently, the libraries obtained for miRNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 107 publications
2
39
0
Order By: Relevance
“…Therefore the reads captured in this study may likely be the fragments of tRNAs but it is not certain if these fragments are representative of mature full length tRNAs or if they represent actual physiological products (identified as tRFs). Nevertheless, we and others45 have confirmed that tRNA sequences can be accurately captured using small RNA sequencing and the reads captured from our study represent the known tRNAs identified and annotated to-date across all chromosomes (Supplementary Table S4). …”
Section: Discussionsupporting
confidence: 76%
“…Therefore the reads captured in this study may likely be the fragments of tRNAs but it is not certain if these fragments are representative of mature full length tRNAs or if they represent actual physiological products (identified as tRFs). Nevertheless, we and others45 have confirmed that tRNA sequences can be accurately captured using small RNA sequencing and the reads captured from our study represent the known tRNAs identified and annotated to-date across all chromosomes (Supplementary Table S4). …”
Section: Discussionsupporting
confidence: 76%
“…Although miRNAs are only one of the many sncRNA species in smRNA-seq data sets, miRNAs remain the most popular class to study, largely because their biogenesis is relatively well understood and because the regulatory mechanism in post-transcription is known (42). However, more and more evidence shows that other non-miRNA sncRNAs also play important roles in gene regulation and certain diseases, such as cancers (5,7,4345). For instance, there is an increasing amount of knowledge regarding the role of snoRNAs in cancer progression, and the information obtained thus far suggests that snoRNAs hold considerable potential for use as novel biomarkers and therapeutic targets in cancer treatment (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a growing number of studies have reported that aberrant piRNA expression is a signature marker across distinct tumor types (3) and that snoRNAs act as oncogenes in tumorigenesis (46). The integration of large-scale smRNA-seq data helps researchers study the roles of these functional sncRNAs in cancer progression, but questions remain concerning the optimal methodologies for analysis, translation and utilization of such massive amounts of data (7). …”
Section: Introductionmentioning
confidence: 99%
“…35,36 In short, library construction from total RNA used the TruSeq Small RNA sample preparation kit (Illumina, San Diego, CA) and sequencing was performed on the Illumina HiSeq2500. Raw sequencing reads in BCL format were processed through CASAVA-1.8.2 for FASTQ conversion and demultiplexing.…”
Section: Methodsmentioning
confidence: 99%